Literature Review: Perbandingan Kekuatan Otot Pasien DM Tipe 2 dan Non-DM pada Lansia - Asmah Aulia; Wiwit Agung Sri Nur Cahyawati; Roselina Panghiyangani (Homeostasis, 2021)
Abstract: Elderly is someone over 60 years of age who experiences a natural aging process characterized by decreased physical ability due to changes in the function of organs and body systems which results in various diseases, one of which is type 2 diabetes. Aging is related to a progressive decrease in skeletal muscle strength. The purpose of this review literature is to determine the differences in muscle strength in patients with type 2 diabetes and non-DM patients in the elderly by analyzing the related literature obtained from search results in medical journal databases, namely Pubmed-MEDLINE and Google Scholar. There are 20 articles included in English and published in 2004-2020. Decreased muscle strength in the elderly due to increased visceral fat and intramuscular fat while subcutaneous fat, the number and size of muscle fibers decreased. The decrease in muscle strength in DM is due to insulin resistance resulting in a decrease in protein synthesis and an increase in protein degradation. So it can be concluded that the elderly with type 2 DM have lower muscle strength than non-DM. Keywords: elderly, muscle strength, diabetes mellitus type 2, non DM, hand grip strength. Abstrak: Lansia adalah seseorang berusia diatas 60 tahun yang mengalami proses penuaan alami ditandai menurunnya kemampuan fisik akibat perubahan fungsi organ dan sistem tubuh yang berakibat pada berbagai penyakit salah satunya DM tipe 2. Penuaan berkaitan dengan menurunnya kekuatan otot rangka secara progresif. Tujuan literatur review ini untuk mengetahui perbedaan kekuatan otot pasien DM tipe 2 dan non DM pada lansia dengan menganalisis literatur terkait yang didapatkan dari hasil pencarian pada database jurnal kedokteran, yaitu Pubmed-MEDLINE dan Google Scholar. Artikel yang disertakan sebanyak 20 menggunakan bahasa inggris dan dipublikasikan pada tahun 2004-2020. Penurunan kekuatan otot pada lansia karena lemak visceral dan lemak intramuscular meningkat sedangkan lemak subkutan, jumlah dan ukuran serat otot menurun. Penurunan kekuatan otot pada DM disebabkan resistensi insulin  sehingga terjadi penurunan sintesis protein dan peningkatan degradasi protein. Sehingga dapat disimpulkan lansia dengan DM tipe 2 memiliki kekuatan otot yang lebih rendah dibandingkan non DM. Kata-kata kunci:  lansia, kekuatan otot, diabetes melitus tipe 2, non DM, hand grip strength.Abstract:Elderly is someone over 60 years of age who experiences a natural aging process characterized by decreased physical ability due to changes in the function of organs and body systems which results in various diseases, one of which is type 2 diabetes. Aging is related to a progressive decrease in skeletal muscle strength. The purpose of this review literature is to determine the differences in muscle strength in patients with type 2 diabetes and non-DM patients in the elderly by analyzing the related literature obtained from search results in medical journal databases, namely Pubmed-MEDLINE and Google Scholar. There are 20 articles included in English and published in 2004-2020. Decreased muscle strength in the elderly due to increased visceral fat and intramuscular fat while subcutaneous fat, the number and size of muscle fibers decreased. The decrease in muscle strength in DM is due to insulin resistance resulting in a decrease in protein synthesis and an increase in protein degradation. So it can be concluded that the elderly with type 2 DM have lower muscle strength than non-DM. Keywords: elderly, muscle strength, diabetes mellitus type 2, non DM, hand grip strength. Abstrak: Lansia adalah seseorang berusia diatas 60 tahun yang mengalami proses penuaan alami ditandai menurunnya kemampuan fisik akibat perubahan fungsi organ dan sistem tubuh yang berakibat pada berbagai penyakit salah satunya DM tipe 2. Penuaan berkaitan dengan menurunnya kekuatan otot rangka secara progresif. Tujuan literatur review ini untuk mengetahui perbedaan kekuatan otot pasien DM tipe 2 dan non DM pada lansia dengan menganalisis literatur terkait yang didapatkan dari hasil pencarian pada database jurnal kedokteran, yaitu Pubmed-MEDLINE dan Google Scholar. Artikel yang disertakan sebanyak 20 menggunakan bahasa inggris dan dipublikasikan pada tahun 2004-2020. Penurunan kekuatan otot pada lansia karena lemak visceral dan lemak intramuscular meningkat sedangkan lemak subkutan, jumlah dan ukuran serat otot menurun. Penurunan kekuatan otot pada DM disebabkan resistensi insulin  sehingga terjadi penurunan sintesis protein dan peningkatan degradasi protein. Sehingga dapat disimpulkan lansia dengan DM tipe 2 memiliki kekuatan otot yang lebih rendah dibandingkan non DM. Kata-kata kunci:  lansia, kekuatan otot, diabetes melitus tipe 2, non DM, hand grip strength.